1991
DOI: 10.1143/jjap.30.l371
|View full text |Cite
|
Sign up to set email alerts
|

Current Density Dependence for Dark-Line Defect Growth Velocity in Strained InGaAs / AlGaAs Quantum Well Laser Diodes

Abstract: Dark-line defects (DLDs) of threading dislocation origin in strained InGaAs/AlGaAs quantum well laser diodes were observed by the electron-beam induced current technique. Current density dependence for the DLD growth velocity was compared quantitatively with that for unstrained GaAs/AlGaAs quantum well laser diodes for the first time. The <110>DLD growth velocity in InGaAs QW laser diodes is estimated to be about 1/100 of that for the <100>DLD growth in the GaAs QW laser diodes, showing linear depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…They found a linear dependence between drive current density and degradation rate, and no discernable dependence on output power. [15] Similar findings have been reported by Fukagai et al for in-plane lasers [16]; James Guenter reported that VCSELs also appeared to have no output power dependence to their degradation [17], which has also been consistent with our findings. The only caution we offer to making this a "blanket rule" is that some failure modes such as <100> DLD growth (not the dominant failure mode in VCSELs) are likely pumped by lateral spontaneous emission.…”
Section: Appendix A: Acceleration Model Validity At High Temperaturessupporting
confidence: 93%
See 2 more Smart Citations
“…They found a linear dependence between drive current density and degradation rate, and no discernable dependence on output power. [15] Similar findings have been reported by Fukagai et al for in-plane lasers [16]; James Guenter reported that VCSELs also appeared to have no output power dependence to their degradation [17], which has also been consistent with our findings. The only caution we offer to making this a "blanket rule" is that some failure modes such as <100> DLD growth (not the dominant failure mode in VCSELs) are likely pumped by lateral spontaneous emission.…”
Section: Appendix A: Acceleration Model Validity At High Temperaturessupporting
confidence: 93%
“…16 16 16 Table 2: Test matrix for 12µm oxide VCSELs used at 6mA average bias current. 16 devices per test condition are adequate to determine the mean lifetime and the distribution parameter.…”
Section: °°°°Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation and reliability discussed in the following part of this section and in the following sections is therefore restricted to lasers with the wells whose thickness is less than the critical thickness. Some researchers have observed long-term stable operation without (100) DLDs, [9][10][11][12][13] although the reason that the (100) DLD scarcely grows or grows at a very low rate in those lasers are not known. This degradation behavior is quite different with lattice-matched AlGaAs/GaAs lasers and AlGaAs/GaAs QW lasers.…”
Section: Nm Lasersmentioning
confidence: 99%